Plasma levels of ghrelin, des-acyl ghrelin and LEAP2 in children with obesity: correlation with age and insulin resistance - Fittipaldi, Antonela Soledad (2020)
Objective: The octanoylated peptide hormone ghrelin regulates appetite and glycaemic control. Des-acyl ghrelin abolishes some effects of ghrelin, but does not bind to ghrelin receptor. LEAP2 is a novel ligand for ghrelin receptor that blocks the effects of ghrelin. Some evidences show that plasma levels of these peptides are altered in adults with obesity, but their levels in childhood obesity remain poorly studied. Therefore, the objective of this study was to assess fasting plasma levels of ghrelin, des-acyl ghrelin and LEAP2 in children with normoweight, overweight/obesity and their association with different anthropometric and metabolic variables. Design: A total of 42 females and 40 males, ages 3–12 years old were enrolled as a cross-sectional cohort. Results: Plasma levels of des-acyl ghrelin and LEAP2 (but not ghrelin) were lower and ghrelin/des-acyl ghrelin ratio was higher in children with overweight/obesity. Des-acyl ghrelin negatively correlated with age, BMI z-score, insulin and HOMA index, and the correlations were stronger in children with overweight/obesity. LEAP2 levels negatively correlated with BMI z-score. No gender differences were found. Conclusions: Our findings suggest that ghrelin tone is increased in childhood obesity, due to a decrease on plasma levels of des-acyl ghrelin and LEAP2, and that des-acyl ghrelin is associated to insulin resistance, particularly in children with overweight/obesity.